Effect of the synthesis parameters of in situ grown Mg-Al LDHs on the filiform corrosion susceptibility of painted AA5005. (10th June 2021) - Fedel, Michele; Zanella, Caterina; Ferrari, Luca; Deflorian, Flavio
Abstract: Novel layered double hydroxides (LDHs) based coatings developed in-situ on aluminum alloys are recognized to provide the substrate with improved corrosion protection. LDH layers have gained prominent attention due to their barrier properties and ions exchange capability, together with compositional flexibility and low environmental impact. In this work, diverse MgAl LDHs layers are developed on AA5005 as a surface conversion treatment prior to applying an acrylic clearcoat. The work aims to assess the potential LDH layers of to improve the filiform corrosion (FFC) resistance of the AA500 substrate. The effect of the synthesis time and the presence of urea on the FFC susceptibility are investigated. The performance of the different synthesis conditions was compared and shown to be more effective to increase FFC resistance when well-defined crystals are formed. The findings suggest that MgAl-LDHs mitigate the extent of filiform corrosion of acrylic paint coated AA5005. The FFC inhibition was found to be qualitatively proportional to the pitting potential measured over the LDHs conversion layers.